Pronunciation Research in the Malaysian Context: A Systematic Review (LSP International Journal, 2017)
This paper presents the current evidence with regard to English pronunciation teaching and learning in the Malaysian context. A systematic literature review (SLR) of empirical studies was conducted with a focus on examining the degree to which pronunciation research is conducted in the context of English as a second language (ESL) in Malaysia. Results showed that teachers’ and learners’ beliefs are critical factors that may improve or impede the pronunciation instruction of the target language. In addition, there are also some criteria that need to be considered in order to ensure the effectiveness of pronunciation teaching for ESL learners. The issue of whether or not Received Pronunciation (RP) can be adopted as the pronunciation model in the Malaysian education system should also be addressed appropriately. These results are significant because they call for a reevaluation of pronunciation instruction in Malaysia. Finally, the findings of this SLR uncovered one of the real challenges in English language teaching, which is to bridge the gap between theory and practice, given the disconnection between research-based models and the actual practices in the ESL classroom